Development of Tissue Culture Book Based on Research on Rooting Induction of Dendrobium Sp. Orchids In Vitro with Combination Media - Sari, Elvira Nanda; Harahap, Fauziyah; Sudibyo , Mufti (Jurnal Perspektif, 2025)
The development of research-based tissue culture books is very necessary considering its limited availability. This study aims to provide a reference book on in vitro root induction of Dendrobium sp. orchids using several media. This development research uses a 4-D (Four-D) model in the development of reference books which are a product or innovation from a particular research result consisting of the stages of definition, design, development and dissemination. Data analysis was carried out using a Likert scale questionnaire to analyze material experts, learning design experts, layout design experts, lecturer responses, and student responses. The analysis used was quantitative and qualitative analysis. The validation results showed that the second material obtained a score of 87.79% with a very good category, validation of learning design experts obtained a score of 95.5%, validation of layout design experts obtained a score of 95%, lecturer responses obtained a score of 855, and student responses calculated from individual trials of 89.33% and small group trials of 91.11%. The N-Gain score test showed that the book could improve the cognitive learning outcomes of tissue culture students. It is determined that the tissue culture book based on research on root induction of Dendrobium sp. orchids with mixed media is possible and useful as a supporting book for learning tissue culture.